백내장 수술 후 시력 저하를 호소하는 환자에서 발견된 뇌하수체 라트케열 낭종 1예 - 김민선; 윤영채; 박선경; 황웅주; 황호식; 김현승; 나경선; 박미라 (검안 및 콘택트렌즈 학회지, 23(2), 2024)
목적: 백내장 수술 이후 시력 저하를 호소하는 환자에서 시야 결손을 유발하는 안장 위 라트케열 낭종을 진단한 1예를 보고하고자 한다. 증례요약: 좌안 백내장 수술 이후 최대교정시력 0.6을 보인 62세 남자 환자가 수술 2달 뒤 좌안 시력 저하로 내원하였다. 내원 시 최대교정시력 0.2, 상대구심동공운동장애는 없었고 안저 검사상 특이 소견이 없었다. 1달 후 전시야검사상 좌안에서 더 저명한 양안상이측 부분 시야결손 소견이 있었고, 신경절세포층 빛간섭단층촬영에서 시야 이상과 일치하는 양안 비측 신경절세포층 두께의 대칭적 감소가 관찰되었다. 또한 안와 자기공명영상에서 뇌하수체 상부에 직경 21 mm 크기의 액상 고체상 종괴가 시신경 교차를 압박하고 있었다. 이에 신경외과에 의뢰하여 나비뼈 경유 종양 제거술을 시행하였고, 조직검사상 라트케열 낭종을 진단하였다. 수술 후 3개월째, 좌안 최대교정시력 0.5로 회복되었으며 시야검사상 암점 소견은 보이지 않았다. 결론: 뇌하수체 안장 위에 발생한 라트케열 낭종이 시야 이상을 야기한 환자의 예를 보고하며, 원인을 알 수 없는 시력 저하를 호소하는 환자에서 신경안과적 평가를 통한 조기 발견과 치료가 중요함을 상기하고자 한다. Purpose: To report a case of suprasellar Rathke's cleft cyst accompanying visual field defect found in a patient complaining of decreased visual acuity after cataract surgery. Case Summary: A 62-year-old male patient who showed a best-corrected visual acuity (BCVA) of 0.6 after left eye cataract surgery visited our hospital two months after surgery with decreased vision. He showed a best corrected visual acuity of 0.2, did not have relative afferent pupillary defect, and there were no specific findings on fundus examination. In the full field perimetry test, partial visual field loss in superior temporal quadrants were found in both eyes, being more prominent in left eye. In ganglion cell layer measurements using optical coherence tomography, a symmetric thinning in the thickness of the nasal ganglion cell layer was observed in both eyes, which was consistent with the visual field test. It was discovered that a liquid solid mass with a diameter of 21 mm in the upper part of the pituitary gland was compressing the optic chiasm in orbit magnetic resonance imaging. The patient was then referred to neurosurgery for pituitary surgery using transsphenoidal approach and diagnosed with Rathke's cleft cyst on histopathologic examination. Three months after surgery, the BCVA has increased to 0.5 and the visual field test showed no scotoma. Conclusions: We report a case that Rathke's cleft cyst above the sella turcica inducing visual disturbances, emphasizing the importance of early detection and treatment through neuroophthalmological evaluation in a patient presenting with unexplained visual impairment. KCI Citation Count: 0